2020
DOI: 10.1016/j.bbrc.2020.01.114
|View full text |Cite
|
Sign up to set email alerts
|

Redefining PTB domain into independently functional dual cores

Abstract: Current understanding of phosphotyrosine binding (PTB) domain is limited. Recently, we revealed a novel atypical phosphotyrosine binding (aPTB) domain in CCM2, making it a dual PTB domaincontaining protein. Since aPTB domain is only 1/3 of the size of typical PTB domain, we explored the possibility to decrease the size of PTB domain and demonstrate that the typical PTB domain can be divided into two similarly structural and functional cores that can independently bind to NPXY motif. Further, we reduced each PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…These studies support the hypothesis that KRIT1 could regulate leukocyte adhesion in general, yet a more recent study reported that CCM3 regulates the release of the 'reserved' pool of granules from neutrophils due to its interaction with the serine/threonine kinase-24 (STK24) [38]. Though the impact of the interaction of CCM3 with STK24 vs. with KRIT1/CCM2 is still in debate [39][40][41], these findings demonstrate that CCM proteins can regulate neutrophil-specific functions. Together, the role of KRIT1 in limiting the response to inflammatory stimuli [25] and the high expression of KRIT1 in neutrophils and other myeloid cells (data not shown), combined with the potential for KRIT1 to regulate neutrophil adhesion via binding to Rap1 [31] or ICAP1a [32][33][34][35][36][37], led us to explore a potential role for KRIT1 in regulating neutrophil function.…”
Section: Introductionsupporting
confidence: 70%
“…These studies support the hypothesis that KRIT1 could regulate leukocyte adhesion in general, yet a more recent study reported that CCM3 regulates the release of the 'reserved' pool of granules from neutrophils due to its interaction with the serine/threonine kinase-24 (STK24) [38]. Though the impact of the interaction of CCM3 with STK24 vs. with KRIT1/CCM2 is still in debate [39][40][41], these findings demonstrate that CCM proteins can regulate neutrophil-specific functions. Together, the role of KRIT1 in limiting the response to inflammatory stimuli [25] and the high expression of KRIT1 in neutrophils and other myeloid cells (data not shown), combined with the potential for KRIT1 to regulate neutrophil adhesion via binding to Rap1 [31] or ICAP1a [32][33][34][35][36][37], led us to explore a potential role for KRIT1 in regulating neutrophil function.…”
Section: Introductionsupporting
confidence: 70%
“…It is made biomarkers, providing insights into the progression of the disease. Finally, elevated CCM protein levels in tumors night suggest their viability as biomarkers across multiple cancers [49][50][51][52][53][54][55][56][57][58][59]. Both main types of progesterone receptors (nPRs and mPRs) might serve as potential biomarkers for genetically influenced diverse cancer subtypes [60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Pathway analysis illuminated functions and disrupted pathways related to these biomarkers, providing insights into disease progression. Additionally, altered CCM protein levels in tumors propose their potential as biomarkers spanning multiple cancers [20,[53][54][55][56][57][58][59][60][61][62][63]. Both progesterone receptor types (nPRs and mPRs) could potentially serve as biomarkers for genetically influenced cancer subtypes [20,[61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%